2016
DOI: 10.1136/bmjquality.u208920.w3611
|View full text |Cite
|
Sign up to set email alerts
|

The Participative Design of an Endoscopy Facility using Lean 3P

Abstract: In the UK, bowel cancer is the second largest cancer killer. Diagnosing people earlier can save lives but demand for endoscopies is increasing and this can put pressure on waiting times.To address this challenge, an endoscopy unit in North East England decided to improve their facilities to increase capacity and create environments that improve the experience of users. This presented a significant opportunity for step change improvement but also a problem in terms of creating designs that meet user requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Box 3 presents an example from the NHS in North East England, which adopted Lean using knowledge from Virginia Mason 45. The Lean 3P method was used to involve stakeholders in simultaneously designing healthcare facilities and service systems 38434446. The example illustrates challenges to participation that may be generally applicable (specifically the perception that patients are unable to contribute because of a lack of knowledge or ability).…”
Section: Lean Qi Methods To Engage Healthcare Stakeholdersmentioning
confidence: 99%
See 1 more Smart Citation
“…Box 3 presents an example from the NHS in North East England, which adopted Lean using knowledge from Virginia Mason 45. The Lean 3P method was used to involve stakeholders in simultaneously designing healthcare facilities and service systems 38434446. The example illustrates challenges to participation that may be generally applicable (specifically the perception that patients are unable to contribute because of a lack of knowledge or ability).…”
Section: Lean Qi Methods To Engage Healthcare Stakeholdersmentioning
confidence: 99%
“…The project showed that Lean 3P design workshops can provide an effective process for engaging a wide range of stakeholders43 and a structured approach for corporate and clinical staff to work together with patient representatives 44. The Lean concept of end-user value contributed to the design process by drawing out the perspectives (clinical, operational, and experiential) of multiple stakeholders in terms of what mattered most to them.…”
Section: Lean Qi Methods To Engage Healthcare Stakeholdersmentioning
confidence: 99%
“…22 The application of Lean 3P to design healthcare facilities has been pioneered by VMMC 44 61-63 and they have reported significant financial benefits as a consequence. 21 43 Beyond our own research, [22][23][24][25][26] there are, to our knowledge, no cases reported in the literature of Lean 3P being applied to design healthcare facilities in the NHS in the UK. This case used the Lean 3P format to operationalise the Lean principles 13 in the design of a new maternity facility.…”
Section: Designmentioning
confidence: 97%
“…21 43 56 Lean 3P is typically comprised of three phases which are: scoping and planning; a time-out participative design workshop; and follow-up and implementation. 25 In the scoping and planning phase, a meeting was held with key stakeholders in the maternity unit to facilitate a diagnostic exercise. The meeting focussed on sharing information about the upcoming time-out 3P design workshop and comprised midwives, healthcare assistants, consultants of various disciplines (e.g.…”
Section: Baseline Measurementmentioning
confidence: 99%
See 1 more Smart Citation